MON-LB004 Understanding the Influence of Endometrial Cancer Risk Factors Using Human Primary Endometrial Organoids - Murphy, Alina R (J Endocr Soc, 2020)
It is unclear how endometrial cancer risk factors such as obesity, high serum testosterone, and high serum levels of the endocrine-disrupting compound bisphenol-A (BPA) influence hormone action to promote carcinogenesis. We hypothesized that obesity, high testosterone, and BPA exposure alters the protective progesterone response in the benign endometrium. Primary human benign endometrial organoids, consisting of both epithelial and stromal cells, were exposed to each of these risk factors in vitro in the presence of cyclic levels of estradiol, progesterone, and testosterone for 14 days. Progesterone response genes HSD17B2, IGFBP1, PAEP, and PRL were measured by real-time qPCR and IHC. First, to simulate obesity, endometrial organoids were cocultured with increasing numbers of human adipocyte spheroids during the hormone treatment. Real-time qPCR analysis revealed dysregulation of expression of HSD17B2 and IGFBP1 by approximately 20% when cocultured with 30 adipocyte spheroids. In addition, PRL protein levels were significantly lower in the stroma of the endometrial organoids. Second, increasing concentrations of BPA and 3nM testosterone individually or in combination were added to endometrial organoids together with the 14-day menstrual cycle hormones. Treatment with 0.6 ng/mL of BPA decreased expression of HSD17B2, IGFBP1, and PAEP by 50% to 80%. However, this effect was not seen in the context of high testosterone, indicating that there may be crosstalk between these two risk factors. In summary, this study demonstrated that adipocytes, BPA exposure, and high testosterone directly alter progesterone action in benign endometrial organoids, suggesting a diminution of the protective effects of progesterone and an increased risk of endometrial cancer.